The Influence of Motivation, Creativity, and Digital Literacy on Gen Z MSMEs Success in West Kalimantan - Yohanes Aga Rodihtia (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Sabda Setia, 2026)
This study aims to examine the influence of entrepreneurial motivation, creativity, and digital literacy on the success of Micro, Small, and Medium Enterprises (MSMEs) managed by Generation Z in West Kalimantan. Generation Z, born and raised in the digital era, possesses unique characteristics in business management, particularly in terms of mindset and technology adoption. This research adopts a quantitative approach with a causal associative design. A total of 100 MSME actors were selected using purposive sampling, with criteria including Generation Z individuals who have operated their businesses for a minimum of six months. The research instrument used was a structured questionnaire developed based on indicators for each variable. The data were analyzed using multiple linear regression with the help of SPSS 27 software. This study is expected to contribute both theoretically and practically to the development of youth-based entrepreneurship and serve as a reference for policymaking in strengthening MSME capacity in the digital era. The main focus of the research is to identify how internal entrepreneurial factors such as motivation and creativity, along with digital readiness, support business success among Generation Z entrepreneurs.